889 ATRIOVENTRICULAR BLOCK, AN UNUSUAL CLINICAL PRESENTATION OF CALCIFIED BICUSPID AORTIC VALVE. (15th December 2022) - Pisani, Elena; Bartolini, Simone; Sani, Francesca; Signorini, Umberto; Milli, Massimo; Beltrami, Matteo
Abstract: Background: Bicuspid aortic valve (BAV) is the most frequent congenital valve disease in adults. It is often associated with other congenital cardiac defects. Sometimes it is associated with aortic dilatation. BAV is an heterogeneous disease with varying valve morphology (asymmetrical cusp size and rafe), annulus geometry and size, asymmetrical calcification of the aortic valve and left ventricular outflow tract. Case Report: A 32 year-old male patient was diagnosed with bicuspid aortic valve after several cardiologic visits for eligibility to competitive sport. Since April 2021 he developed a progressive exertional dyspnea for strenuous efforts. In February 2022, he was referred to our department after a Holter ECG showed a bradyarrhythmia with complete atrioventricular block. The echocardiography evaluation demonstrated a preserved ejection fraction and a bicuspid aortic valve with a mild-moderate regurgitation. The coronary computed tomography showed a thick and calcified bicuspid aortic valve with a coarse calcification of the anterior cuspid that involve the pars membranacea of the interventricular septum. The ergometric exercise demonstrated chronotropy incompetence. The tomography confirmed the mildy aortic root dilatation. Therefore, an MRI was performed and reported a small laminar LGE on the infero-lateral wall of the left ventricle, of unclear significance. He underwent Dual-Chamber permanent pacemaker implantation. A conservative approach was preferred over valvular replacement, considering the mild aortic root dilatation on a background of mild-to- moderate aortic insufficiency. Conclusion: Our case is unusual given the bicuspid aortic valve concomitant with atrioventricular block, which was connected with the location of the calcification. Thus, the aim of our case report is, to describe a complication to this condition which, although rare, represents a different clinical presentation of the pathology itself in a young adult.